Distribution of Boron in Salt Affected and Contiguous Normal Soils - Bhargava, G P; Singhla, S K; Gupta, I C (Annals of Arid Zone, 2016)
Studies have been carried out on the distribution of soluble boron in secondary salinised soils (1) Natraqualfs and (2) Ustorthents. Boron in saturation extract of soils is significantly positively correlated with pH, EC, ESP and soluble ions in Natraqualfs only.